Superhydrophobic carbon papers for electrostatic water collection from fog - Xie Qiongdan; Yang BeiEr; Mu Jiangtao; Zhang Haoran; Yu Jiaxin; Liu Yunchen; Fang Deyu; Cong Longqi; Yang Qihang; Liu Ruoqi; Chen Qianqian (E3S Web of Conferences)
Fog collection presents a promising solution to water scarcity in arid regions. Typically, hydrophilic surfaces are used for this purpose. This study demonstrates that electrically conductive PTFE-coated superhydrophobic carbon papers are highly effective for electrostatic fog collection. The wettability of the carbon paper has minimal impact on collection efficiency. Despite the superhydrophobic nature of the carbon papers causing condensed fog particles to aggregate into spherical droplets, this aggregation has little effect on collection performance. Additionally, the efficiency of fog collection is independent of charge type; both negative and positive high voltages yield similar results. The fog collection efficiency is directly correlated with electrostatic air current, though the relationship is nonlinear: efficiency initially increases sharply with current before leveling off.